Exploring Amino Acid Auxotrophy in Bifidobacterium bifidum PRL2010 - Ferrario, Chiara; Duranti, Sabrina; Milani, Christian; Mancabelli, Leonardo; Lugli, Gabriele A.; Turroni, Francesca; Mangifesta, Marta; Viappiani, Alice; Ossiprandi, Maria C.; van Sinderen, Douwe; Ventura, Marco (Frontiers in Microbiology, 2015)
The acquisition and assimilation strategies followed by members of the infant gut microbiota to retrieve nitrogen from the gut lumen are still largely unknown. In particular, no information on these metabolic processes is available regarding bifidobacteria, which are among the first microbial colonizers of the human intestine. Here, evaluation of amino acid auxotrophy and prototrophy of Bifidobacterium bifidum, with particular emphasis on B. bifidum strain PRL2010 (LMG S-28692), revealed a putative auxotrophy for cysteine. In addition, we hypothesized that cysteine plays a role in the oxidative stress response in B. bifidum. The use of glutathione as an alternative reduced sulfur compound did not alleviate cysteine auxotrophy of this strain, though it was shown to stimulate expression of the genes involved in cysteine biosynthesis, reminiscent of oxidative stress response. When PRL2010 was grown on a medium containing complex substrates, such as whey proteins or casein hydrolysate, we noticed a distinct growth-promoting effect of these compounds. Transcriptional analysis involving B. bifidum PRL2010 cultivated on whey proteins or casein hydrolysate revealed that the biosynthetic pathways for cysteine and methionine are modulated by the presence of casein hydrolysate. Such findings support the notion that certain complex substrates may act as potential prebiotics for bifidobacteria in their ecological niche.